A scoping review of the contralateral effects of unilateral peripheral stimulation on neuromuscular function. - Shi Zhou; Shuang-Shuang Zhang; Zachary J Crowley-McHattan (PLoS ONE)
It is known that resistance exercise using one limb can affect motor function of both the exercised limb and the unexercised contralateral limb, a phenomenon termed cross-education. It has been suggested that cross-education has clinical implications, e.g. in rehabilitation for orthopaedic conditions or post-stroke paresis. Much of the research on the contralateral effect of unilateral intervention on motor output is based on voluntary exercise. This scoping review aimed to map the characteristics of current literature on the cross-education caused by three most frequently utilised peripheral neuromuscular stimulation modalities in this context: electrical stimulation, mechanical vibration and percutaneous needling, that may direct future research and translate to clinical practice. A systematic search of relevant databases (Ebsco, ProQuest, PubMed, Scopus, Web of Science) through to the end of 2020 was conducted following the PRISMA Extension for Scoping Review. Empirical studies on human participants that applied a unilateral peripheral neuromuscular stimulation and assessed neuromuscular function of the stimulated and/or the unstimulated side were selected. By reading the full text, the demographic characteristics, context, design, methods and major findings of the studies were synthesised. The results found that 83 studies were eligible for the review, with the majority (53) utilised electrical stimulation whilst those applied vibration (18) or needling (12) were emerging. Although the contralateral effects appeared to be robust, only 31 studies claimed to be in the context of cross-education, and 25 investigated on clinical patients. The underlying mechanism for the contralateral effects induced by unilateral peripheral stimulation remains unclear. The findings suggest a need to enhance the awareness of cross-education caused by peripheral stimulation, to help improve the translation of theoretical concepts to clinical practice, and aid in developing well-designed clinical trials to determine the efficacy of cross-education therapies.